Hippocampal neuronal damage in rats exposed to a double hit: irradiation and hyperthermia - (:unkn) unknown (My University, 2011)
AIM: In utero irradiation models induce diffuse neuronal damage. Experimental studies have shown that hyperthermia induced seizures are easily elicited and have high mortality accompanied by neuronal loss. Neuronal damage and loss are the results of cell death coupled with cortical development in altered cellular development. The aim of the study was to investigate the changes in hippocampus that was exposed to irradiation and hyperthermia. MATERIAL AND METHODS: Four groups were studied: 1) The irradiation group was exposed to 225 cGy irradiation on the 17th gestational day; 2) The hyperthermia group was exposed to hyperthermia on the 10th postnatal day; 3) The hyperthermia plus irradiation group was exposed to in utero irradiation and postnatal hyperthermia; 4) The control group was sham operated. Animals were examined 3 and 6 months later. RESULTS: The hippocampus was atrophic with neuronal loss in CA regions and ectopic neurons were in irradiation group. Severe damage with the most atrophy was demonstrated in all regions of the irradiation plus hyperthermia group. In long term, damage was severe in all groups. CONCLUSION: This study demonstrated more damage in hippocampi exposed to both irradiation and hyperthermia that may be taken as an evidence for the double hit hypothesis in the development of hippocampal damage.
Keywords: Female; Pregnancy; Animals; Rats; Cell Count; Rats, Wistar; Radiation Injuries; Behavior, Animal; Hippocampus; Radiation Dosage; Fever; Pyramidal Cells; Prenatal Exposure Delayed Effects; Nerve Degeneration; Cobalt Radioisotopes